Is there any difference between pregnancy results after tubal reanastamosis performed laparotomically, laparoscopically, and robotically? - (:unkn) unknown (WILEY, 2022)
Introduction: Tubal reanastamosis offers hope to conceive again. However, there are many factors that affect the success of this procedure. In our study we aimed to compare the pregnancy rates of the surgical methods used for tubal reanastamosis in pregnancy requested after tubal sterilization. Methods: In our study we compared the rates of pregnancies after reanastamosis retrospectively in female patients under the age of 40 who underwent reanastamosis between 2010 and 2019 with laparotomic, laparoscopic and robotic methods. A single layer of 4 quadrant 6/0 number polydioxanone absorbable sutures were used in all surgical methods. A similar surgical technique was used. Results: In surgical methods (laparotomy, laparoscopy, and robotics), there was a statistical difference between the three groups in terms of operation times of surgical methods used for tubal reanastamosis (p < 0.05). Laparotomy, laparoscopy, and robotics pregnancy rates were 52.6% (n = 41), 67.3% (n = 37), 61.2% (n = 63), respectively. There was no statistical difference between groups in terms of pregnancy rates. However, odds ratio (OR) values of the laparoscopy group and robotics group probability of conception were 1.536 (95% confidence interval [CI], 0.813-2.898), 1.111 (95% CI, 0.656-1.879) higher, respectively. Conclusions: Although there is no statistical difference between the surgical methods used for tubal reanastamosis, we think that the laparoscopic surgical method may be preferable due to the shorter hospital stay. We think that the previous method of bilateral tubaligastion (BTL), the site of reanastasis, and the time between BTL and reanastomosis were effective in pregnancy success.
Keywords: sterilization reversal; surgical methods; tubal reanastamosis; MICROSURGICAL REVERSAL; STERILIZATION REVERSAL; RE-ANASTOMOSIS